Revision of the world species of the genus Fusicornia Risbec (Hymenoptera: Platygastridae, Scelioninae) - Charuwat, Taekul; Norman, Johnson F.; Lubomír, Masner; Rajmohana, K.; Chen, Shu-Pei (Zootaxa, 2008)
The genus Fusicornia Risbec (Hymenoptera: Platygastridae, Scelioninae) is a widespread group in the tropics of the Eastern Hemisphere, distributed from West Africa to Vanuatu. All scelionines are egg parasitoids of arthropods, but the host of Fusicornia is not yet known. The species concepts are revised and a key to world species is presented. The genus is comprised of 19 species, including five known species which are redescribed: F. bambeyi Risbec (sub-Saharan Africa, Madagascar, Yemen); F. indica Mani & Sharma (Australia, India, Philippines, Sri Lanka, Thailand); F. koreica Choi & Kozlov (China, Japan, Korea, Philippines); F. spinosa (Risbec) (sub-Saharan Africa, Saudi Arabia, United Arab Emirates, Yemen); and F. tehrii Mukerjee (Brunei, Indonesia, Japan, Laos, Malaysia, Papua New Guinea, Philippines, Sri Lanka, Taiwan, Thailand). Fusicornia noonae Buhl is considered to be a junior synonym of F. tehrii Mukerjee, n. syn., and F. bambeyi var. inermis Risbec is considered to be a junior synonym of F. spinosa (Risbec), n. syn. The following species are hypothesized and described as new taxa: F. ardis Taekul & Johnson, n. sp. (West Africa, Kenya, Tanzania); F. aulacis Taekul & Johnson, n. sp. (Madagascar); F. collaris Taekul & Johnson, n. sp. (New Guinea); F. crista Taekul & Johnson, n. sp. (Somalia, Tanzania); F. dissita Taekul & Johnson, n. sp. (Vanuatu); F. eos Taekul & Johnson, n. sp. (West Africa, Tanzania, Yemen); F. episcopus Taekul & Johnson, n. sp. (Thailand); F. fax Taekul & Johnson, n. sp. (Papua New Guinea); F. fortuna Taekul & Johnson, n. sp. (Madagascar, Yemen); F. paradisa Taekul & Johnson, n. sp. (sub-Saharan Africa, Madagascar); F. plicata Taekul & Johnson, n. sp. (Sri Lanka); F. skopelos Taekul & Johnson, n. sp. (Madagascar); F. sabrina Taekul & Johnson, n. sp. (Somalia) and F. speculum Taekul & Johnson, n. sp. (Central African Republic, Madagascar, Nigeria, Uganda).